Indians of the Northeast : traditions, history, legends, and life - Sita, Lisa, 1962- (Philadelphia ; London : Courage Books, 1997)
Describes the Native American tribes of the Northeast and their history and culture both before and after contact with Europeans
Includes bibliographical references (p. 62) and index
Keywords: Indians of North America -- Northeastern States